Analysis Of The Installation Of Subsea Pipelines To Support The Need For Clean Water In Supporting Tourism Development On Kayangan Island - Palippui, Habibi (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2022)
Inclusive access to water is very important for the tourism sector to maintain a good reputation among tourists and the social license of the local community to operate. While all stakeholders or stakeholders expect the success of tourism which contributes to economic improvement, community welfare, human resource development, and improvement of public health and the environment, tourism activities on Kayangan Island need clean water for their development. Considering that the island is one of the favourite tourist destinations and is growing quite rapidly at this time, there is no effective source of clean water available on the island. Therefore, it can be attempted to provide clean water by using subsea pipes sourced from PDAM Makassar. According to observations from various aspects, the pipe will cross the ocean with a span of ±1500 meters by flowing water with a discharge of 10 lt/s using HDPE pipes with a diameter of 140mm PE100, PN 16 according to SNI standards. For a fairly good security system, the jet pump and the pipe will be tied to a 110 mm diameter stainless steel sling bridge. In addition, at every 6 meters distance, the pipe bridge slings are fitted with ballast loads with hanging slings. In this study, the installation of subsea pipelines requires a variety of supporting equipment and also a complicated implementation, but it is can be carried out considering this needs to be done to support the need for clean water on Kayangan Island to support tourism development.